SCIENTIFIC RESEARCH PREPARATION OF FUTURE SPECIALISTS OF THE SOCIAL SPHERE AT THE UNIVERSITIES OF THE USA - Povidaichyk, Oksana; Varga, Nataliya (Social work and education, 2019)
The article reveals the peculiarities of preparation of specialists of the social sphere for scientific research activity in the high school of the United States. It has been proved that the structure of knowledge of scientific research activity of graduates of the university must include: a) general methodological and general scientific laws and principles; b) the provisions of scientific and cognitive activity and the methods of scientific research based on them; c) principles and methods of researches, applied in various spheres of social practice. Scientific research preparation is carried out in several forms: research blocks are included into the general and profile disciplines; in the framework of studying of the specialized courses; in the process of development of research projects; during the practice, an obligatory component of which is an independent research study. It has been found out that the experience of organizing and conducting of the researches is acquired by students in the framework of the study of discipline «Researches in social work». The discipline is aimed at familiarizing students with the research methodology, the specifics of working with scientific and professional literature, mastering the research methods as well as the peculiarities of developing of a research projects, the methods of data analysis and interpretation of the results of the study with a purpose of their practical application, writing a report on the work done. Scientific research preparation of students involves the use of such forms and methods as: work with the cases, modelling, training in the natural environment, instruction, teamwork, group project work, game techniques, writing essays. Typical trends of scientific research preparation in the high school of the US, which should be considered in Ukraine, are: fundamentalization of education, which is expressed in the strengthening of the scientific basis through the inclusion of theoretical courses and problems with the elements of research into the educational programs; involvement of qualified professionals into the teaching process; research orientation of educational disciplines on solving the needs of practice, implemented through the introduction into the curriculum a significant number of hours of practice in social agencies providing «research space» for students.